Alpine skiing and snowboarding training system using induced virtual environment - Aleshin, V.; Klimenko, S.; Manuilov, M.; Melnikov, L. (Science and Skiing IV, 2009)
INTROOUCTION: The proposed ski training System is intended for Alpine skiing and snowboarding training (Aleshin & Danilin, 2002). It is developed on the basis of a unique ski trainer SkyTec Interactive (Trainer SkyTec Interactive) and stereoscopic virtual environment System (Aleshin, Afanasiev, Klimenko et al., 2004). The training System simulates both dynamic loads on a skier and his 3D visual perception of a slope.